CHI3L1 plays a role in cancer through enhanced production of pro-inflammatory/pro-tumorigenic and angiogenic factors - Libreros, Stephania (2013)
Elevated serum levels of a glycoprotein known as chitinase-3-like protein 1 (CHI3L1) have been correlated with poor prognosis and shorter survival of patients with cancer and inflammatory diseases. The biological and physiological functions of CHI3L1 in cancer have not yet been completely elucidated. In this review, we describe the role of CHI3L1 in inducing pro-inflammatory/pro-tumorigenic and angiogenic factors that could promote tumor growth and metastasis.